Association of BMI with Hypertension among the Selective Patients in Chattogram - Hossain, Mohammed Akram; Chowdhury, Mohammed Ibrahim; Azad, Md Saifudddin; Chowdhury, MSI Tipu; Nasrin, Kishuar; Dey, Rajiv; Bashiruddin, ABK; Azim, Mohammed Noorul (IAHS Medical Journal, 2024)
Background: Body Mass Index is one of the significant determinant associated with many disease process particularly hypertension. There is positive association between Body Mass Index (BMI) and Blood Pressure (BP). Lowering BMI with weight reduction significantly reduces Blood Pressure (BP). The main purpose of this study was to find out the association of BMI with hypertension. The aim of the study is to find out any association between BMI and hypertension in Chattogram. Materials and methods: It was a cross-sectional study done from June to December 2023 in private chamber among hypertensive patients aged 20 years and above. 188 hypertensive patients were included in the study. BMI was calculated by a person’s weight in kilograms divided by height in meters squared. Results: In this study-it is observed that majority 125(66.4%) of the patients belonged to age between 40-70 years, 104(52%) were male, 18(9%) were graduates and 95(47%) were service holder. Out of 188 hypertensive patients, 77(38.5%) were overweight and 26(13%) were obese. Conclusion: High BMI increases the risk of HTN. IAHS Medical Journal Vol 7(1), June 2024; 65-67